TAKHRIJ HADIS BACAAN WUKUF DI ARAFAH - Winda Sari (UIN Sumatera Utara Medan, 2019)
Hajj is one of the pillars of Islam. Hajj orders must be carried out by every Muslim who has the ability. The ability of a Muslim to perform the Hajj is different from the ability to do other worship. This is related to the implementation of which has special provisions of time and place, different from other services such as prayer and zakat. Prayers and zakat have provisions for implementation time without any provisions regarding the place of implementation. This makes the Hajj more special than other worship. So that the implementation is even in accordance with the guidance of the Koran and Hadith. Among them is about the sunnah readings that are spoken in each series of the implementation of the Hajj.